(untitled) (EAAE Annual Conference Proceedings, 2025)
In response to the significant transformation of knowledge, society, and culture brought about by digital capabilities, architects are increasingly focused on creating, preserving, and interpreting knowledge while utilizing computational methods to read user experiences. With the advancement of digital tools and data analytics platforms, we can effectively interpret and communicate complex data, analyze spatial relationships, reveal connections, and gain deeper insights into user experiences. By visualizing user experiences and relating our research to the networked information age, we can review existing research practices and provide new perspectives on experience, as well as alternative modes of knowledge production. As architecture continues to incorporate technology in design and analysis, engaging with data analytics has the potential to stimulate innovative pedagogical approaches in architectural education. This emphasizes the importance of interdisciplinary learning and the integration of advanced digital tools and methodologies. Such a progressive approach fosters critical thinking and creativity, equipping future architects to address the complexities of contemporary society with data-driven insight. This proposed paper aims to explore the potential of data visualization in reading complex data, analyzing spatial relationships and patterns, revealing connections, and providing insights into research processes and outcomes. The research was conducted in an undergraduate architectural course that examined the user experience of an archaeological museum. This museum houses artifacts from various periods, each with its own material and cultural significance. The specific objectives of this study are to present a fresh perspective on the museum experience, uncover new relationships within the collection, and introduce a new layer of information based on user experience data. By situating this research within the context of the networked information age, it seeks to establish a global, trans-historical, and transmedia approach to knowledge and meaning-making. This research study aims to facilitate an exploration of both the visible and invisible aspects of a museum collection and its user experience by promoting comprehensive research on data visualization.